Bacterial spore inactivation by non-thermal technologies: resistance and inactivation mechanisms. (December 2021) - Lv, Ruiling; Liu, Donghong; Zhou, Jianwei
Highlights: Spores were highly resistant to both thermal and non-thermal processing. The inactivation mechanism of each processing was different. High-pressure process induced the germination of spores. Non-thermal processing usually applied as hurdle technologies. Abstract : Thermal processing remains the major technology in food industry while it inevitably destructs sensory, nutrition and functional ingredients of food. In recent years, there has been a growing interest in non-thermal process. Spores are the dormant state of vegetative cells and have unique multilayers structure. A lot of research focused on the inactivation of spores due to its extremely resistance. This review focused on the inactivation effects and mechanisms of spores by non-thermal processing. High-pressure processing inactivated spores by two step pathways. First moderate high pressure induced the germination of spores, and the resistance decreased rapidly. Then the germinated spores inactivated as followed. Some non-thermal techniques such as ultrasound and ultraviolet radiation had synergistic effects and were usually applied as hurdle technologies.